2010
DOI: 10.1167/iovs.09-3467
|View full text |Cite
|
Sign up to set email alerts
|

Silent Substitution Stimulation of S-cone Pathway and L- and M-cone Pathway in Glaucoma

Abstract: Glaucoma and its severity were objectively detected by using the silent substitution technique. The stimulation technique and signal analysis enabled assessment of the visual evoked potentials of individual color channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
(58 reference statements)
0
10
0
1
Order By: Relevance
“…As mentioned above, this study teased out rod-and medium-to long-wavelength cone subtypespecific contributions to the mouse flicker ERG under identical adaptation conditions. Compared with mice, spectral isolation of individual photoreceptor types in the human retina has received more attention (Bessler et al 2010;Brainard et al 2000;Cao et al 2011;Challa et al 2010;Kremers et al 2000Kremers et al , 2009Kremers and Link 2008;Kremers and Scholl 2001), which has allowed more detailed investigations. Even so, few have examined rod-only contributions to the flicker ERG (Cao et al 2011;Kremers and Pangeni 2012), because its isolation from S-cones with reasonable strength is difficult [i.e., max of S-cone ϳ 435 nm vs. rod ϳ 495 nm (Kraft et al 1993;Stockman and Sharpe 2000)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, this study teased out rod-and medium-to long-wavelength cone subtypespecific contributions to the mouse flicker ERG under identical adaptation conditions. Compared with mice, spectral isolation of individual photoreceptor types in the human retina has received more attention (Bessler et al 2010;Brainard et al 2000;Cao et al 2011;Challa et al 2010;Kremers et al 2000Kremers et al , 2009Kremers and Link 2008;Kremers and Scholl 2001), which has allowed more detailed investigations. Even so, few have examined rod-only contributions to the flicker ERG (Cao et al 2011;Kremers and Pangeni 2012), because its isolation from S-cones with reasonable strength is difficult [i.e., max of S-cone ϳ 435 nm vs. rod ϳ 495 nm (Kraft et al 1993;Stockman and Sharpe 2000)].…”
Section: Discussionmentioning
confidence: 99%
“…Today, the method is commonly used in human electrophysiology and psychophysics (Bessler et al 2010;Kremers et al 1999Kremers et al , 2003Shapiro et al 1996;Usui et al 1998aUsui et al , 1998bZele et al 2006). This method has several advantages relative to the selective adaptation method, because the isolation of different photoreceptor types can be achieved without changing the state of adaptation.…”
mentioning
confidence: 99%
“…44 These complex changes in latency with disease progression suggests the involvement of multiple processes and may be linked to proposals of the loss of different RGC and other neuron types at different stages of glaucoma. 25,[45][46][47][48][49][50] For example, one could imagine a decrease in latency caused by early damage to a slower pathway countering a gradual increase in latencies caused by slowly accumulating damage to a faster pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar: 1 mm. (Bayer et al, 2001;Calkins, 2012); (ii) in monkey OHT models analyzed with anatomical techniques (Nork, 2000;Nork et al, 2000) or with functional techniques (Liu et al, 2014;Nork et al, 2014); and (iii) in human GONs analyzed with functional (Barboni et al, 2011;Bessler et al, 2010;Drasdo et al, 2001;Holopigian et al, 1990;Kanis et al, 2010;Niwa et al, 2014;Velten et al, 2001;Werner et al, 2011) or anatomical Kanis et al, 2010;Lei et al, 2008Lei et al, , 2011Nork, 2000;Nork et al, 2000;Panda and Jonas, 1992;Werner et al, 2011) techniques. The above reviewed results appear to be in contrast with previous studies that have not found cone photoreceptor loss in OHT monkey (Wygnanski et al, 1995) or human (Kendell et al, 1995) retinas.…”
Section: Oht Affects the Orlsmentioning
confidence: 99%